Lessons from the Pandemic: Technology and Protection for Human Rights in the New Normal Era - Murtadho, Ershad (Kathmandu School of Law Review, 2020)
With millions of people diagnosed with Coronavirus disease (“COVID-19”) till date, state governments have turned to using technologies such as contact tracing systems, high-tech camera sensors, or even information surveillance to control the spread of the pandemic. Despite the numerous advantages these technologies have produced, for example, swiftly flattening the infection curve and enforcing health protocols, the implications of maintaining such use of technologies in upholding fundamental human rights going into the post-pandemic ‘new normal’ era is not clear. Experts have debated the compliance of technologies to respect one’s right to privacy and right to freedom of expression when achieving their protective purposes to uphold societies’ right to the enjoyment of health during the pandemic. However, knowing the continuous improvement of technology, and mindful of the absence of the absolute certainty of its usage in the new normal era, whether it relates to the mechanism or the temporal length of its employment, this paper will further delve into such debate in the context of a pandemic-free environment. After considering the different forms and usages of technologies during the pandemic, analyzing the advantages of using technologies in the future, and critically assessing such usages from the perspective of international human rights law (“IHRL”), this paper claims that the technologies which are used during the pandemic must be properly maintained coming into the new normal era. However, several parameters; mainly the functionality of the technology, participation from the general public, and the formation of an appropriate legal framework, will have to become the main focus of governments to ensure the compliance of technologies with IHRL standards.